Naturalism and the hard problem of mysticism in psychedelic science - Jylkkä, Jussi (Frontiers in Psychology, 2024)
Psychedelic substances are known to facilitate mystical-type experiences which can include metaphysical beliefs about the fundamental nature of reality. Such insights have been criticized as being incompatible with naturalism and therefore false. This leads to two problems. The easy problem is to elaborate on what is meant by the "fundamental nature of reality", and whether mystical-type conceptions of it are compatible with naturalism. The hard problem is to show how mystical-type insights, which from the naturalistic perspective are brain processes, could afford insight into the nature of reality beyond the brain. I argue that naturalism is less restrictive than commonly assumed, allowing that reality can be more than what science can convey. I propose that what the mystic refers to as the ultimate nature of reality can be considered as its representation-and observation-independent nature, and that mystical-type conceptions of it can be compatible with science. However, showing why the claims of the mystic would be true requires answering the hard problem. I argue that we can in fact directly know the fundamental nature of one specific part of reality, namely our own consciousness. Psychedelics may amplify our awareness of what consciousness is in itself, beyond our conceptual models about it. Moreover, psychedelics may aid us to become aware of the limits of our models of reality. However, it is far from clear how mysticaltype experience could afford access to the fundamental nature of reality at large, beyond one's individual consciousness. I conclude that mystical-type conceptions about reality may be compatible with naturalism, but not verifiable.